Detection of residual cognitive function through non-spontaneous eye movement in a patient with advanced frontotemporal dementia - Midorikawa, Akira; Itoi, Chihiro; Kawamura, Mitsuru (Frontiers in Neuroscience, 2014)
As dementia progresses, the cognitive functioning of patients declines, and caregivers and other support staff gradually lose the means to communicate with them. However, some caregivers believe that patients can still recognize their surroundings even when they become akinetic with mutism. In this study, we observed eye-movements (preferential looking paradigm) to detect the presence of residual cognitive functions in a patient with severe frontotemporal dementia. The subject was a 76-year-old female. At the time of observation, she had lost all spontaneous activities. Magnetic resonance imaging (MRI) imaging showed dense atrophy in the bilateral frontotemporal lobe, but the parieto–occipital lobe was preserved. A preferential looking paradigm was used in the experiment whereby two different faces (learned and non-learned) were simultaneously presented to the patient on a TV monitor. As a result, we found no significant differences in looking time between the two faces. However, when the saccade timing to the presented faces was examined, a much longer latency was observed for the right rather than the left side of the target faces. Even though the patient had lost all capacity for spontaneous activity, we were able to observe partial residual cognitive ability using the eye-movement paradigm.